ECOLOGICAL ASSESSMENT OF THE HUMAN -TRANSFORMED SYSTEMS OF THE IRPIN RIVER - Madzhd, Svitlana; Kulynych, Yana; Iavniuk, Adrian (Proceedings of National Aviation University (archive), 2017)
Purpose: to learn the interaction of natural and anthropogenic factors and their consequences in the system “Natural environment (Irpin river) – human-transformed environment (Nyvka river)”. Methods: To assess the structural and functional changes of hydroecosystems, transformed under technogenic impact, hydrochemical, toxicological and biological techniques, as well as the methods of mathematical statistics for experimental data processing and summarization of obtained results, were applied. Results: it is proposed to determine the dynamics of the biotic self-regulation mechanism change under impact of the modifying (anthropogenic) factors, by the example of the two-component system – “Natural environment (Irpin River) – environment, transformed under technogenic impact (Nyvka River, the right-hand tributary of the Irpin River)”. It is proposed to extend additionally the opportunities of the ecological assessment due to application of the integrating index – the index of ecological conformity. Discussion: obtained results stipulate necessity of the further investigation of structural and functional patterns of the Irpin River ecosystem in space and time. Assessment of anthropogenic factors impact on hydroecosystem condition will make it possible to correct the nature guard activity concerning the improvement of the fishery object ecological condition and recreation essence of the Irpin River. Integration of the Nyvka and Irpin Rivers into a single system “Natural environment – environment, transformed under technogenic impact” will make it possible to obtain the objective assessment of technogenic changes in hydroecosystems. Implementation of the index of ecological conformity will make it possible to estimate completely the inner processes in the rivers.